Use of affordable hardware and free web based tools for Control Systems laboratory experiments. Issue 9 (2019) - Aguirre, Adriana; Salazar, Carlos; Lema, Alexis; Martin, Cesar
Abstract: Nowadays is more important to implement strategies for control education related to the challenge of using interactive and free web tools. Time is a resource that has become increasingly scarce within the education plan of our University. It is thus, that it has become imperishable to know and take advantage of TICs to encourage the maximum use of activities associated with learning and feedback of results in an effective and dynamic way that promotes active participation of students. This paper presents a methodology to develop laboratory experiments by using hardware and software reliying on this challenge for control education.